Trajectory Tracking and Collision Avoidance Control for Dredging Support Vessels in Automatic Mode Based on Potential Field and Adaptive Sliding Mode Technique - Nguyễn, Hữu Quyền; Trương, Công Mỹ (Journal of Transportation Science and Technology, 2026)
This paper investigates a trajectory tracking and automatic collision avoidance control solution for dredging support vessels operating in automatic mode. These vessels exhibit complex dynamic characteristics due to continuous mass variations and confined working environments with high traffic density. The research employs the Potential Field algorithm to establish a safety path planning mechanism, enabling the vessel to perceive and automatically evade obstacles via virtual repulsive forces. To execute precise trajectory tracking, an Adaptive Sliding Mode Control (ASMC) scheme is designed to ensure system robustness against model uncertainties and environmental disturbances such as waves, wind, and currents. Controller parameters are updated online to eliminate chattering effects and adapt to the vessel’s changing states. Simulation results in MATLAB/Simulink confirm the effectiveness of the proposed method in maintaining high tracking accuracy and ensuring maritime safety, contributing to the enhanced automated operational efficiency of offshore construction vessels